MARKETING MIX AFFECTING USING ENGLISH LANGUAGE SCHOOL SERVICE DECISION OF HIGH SCHOOL STUDENTS IN BANGKOK - ย้อยสวัสดิ์ ลีลาพรรษ์; หิรัญญสมบูรณ์ กตัญญู (Journal of KMITL Business school, 2017)
The objectives of this research were 1) To study the opinion level of marketing mix affecting using english language school service decision of high school students in Bangkok 2) To compare the opinion level of marketing mix affecting using english language school service decision of high school students in Bangkok divided by personal factors. The samples were 400 persons of high school students in Bangkok area selected by accidental sampling method. Questionnaires were used to collect data. Statistics for data analysis were percentage, arithmetic mean and standard deviation. t-test and One-way ANOVA were used for hypothesis testing. The results were as follows: In overall, the opinion level of the marketing mix affecting using english language school service decision of high school students in Bangkok was the highest. The highest opinion of marketing mix was physical evidence, followed by process, people, product, place, promotion and price respectively. Consumers who had different gender, age and education level had different opinion level of marketing mix affecting using english language school service decision of high school students, but the consumers with different study program, guardian’s income and types of school had no difference in the opinion level of marketing mix affecting using english language school service decision of high school students.